Synthesis, In-silico and In-vitro Antimycobacterial Studies on Novel Benzofuran Derivatives - Shelke, Dnyaneshwar E.; Thorat, Bapu R.; Dhabarde, Sanjay S.; Mali, Suraj N. (Current Enzyme Inhibition, 2023)
Background: Benzofurans, interesting heterocyclic compounds, are available abundantly in nature and show a wider range of pharmacological activities. Moreover, in recent years this moiety has been found to have strong antituberculosis potential. Considering the importance of this moiety in the field of medicinal chemistry, we have synthesized a few benzofuran derivatives. Methods: These derivatives were also characterized by standard spectroscopic methods. Synthesized compounds were observed for their anti-tuberculosis activity using microplate Alamar Blue assay (MABA) assay and found to have a minimum of 100 (μg/mL) of minimum inhibitory concentration (MIC) values. Moreover, our molecular docking analyses depicted strong inhibitory potential against a popular TB target, Decaprenylphosphoryl-β-d-ribose 2′-epimerase (DprE1), a crucial enzyme for cell wall synthesis. Results: Compound 9e was found to have a strong binding energy score of -148.47 kcal/mol against the selected targets (PDB id: 6HEZ). Conclusion: All compounds were also found to possess drug-likeness characteristics when checked with Lipinski's filter.
Keywords: in- vitro antimycobacterial studies